Psychosocial characteristics of alcoholic and non-alcoholic liver disease recipient candidates in liver transplantation: a prospective observational study - Masato Shizuku (BMC, 2021)
Abstract Background There are long-standing controversies about the transplant indications for alcoholic liver disease (ALD), because of the recognition that ALD is fundamentally self-inflicted. However, it is unclear whether psychosocial characteristics of ALD are different from that of non-alcoholic liver disease (NALD) in the selection of liver transplantation (LT) recipients. We aimed to clarify the psychosocial characteristics of ALD recipients (ALD-R)/ALD recipient candidates (ALD-RC) and NALD recipients (NALD-R)/ NALD recipient candidates (NALD-RC). Methods From 2011 to 2019, 75 patients were enrolled in this prospective observational study (ALD-RC, n = 19; NALD-RC, n = 56), LT were carried out as follow; ALD-R, n = 6; NALD-R, n = 52. We evaluated psychosocial characteristics in the preoperative period and 3, 12 months after LT (ALD-R, n = 3/3; NALD-R, n = 28/25). The following scales were used to evaluate psychosocial characteristics: Visual Analogue Scale, Alcohol Use Disorders Identification Test, Hospital Anxiety and Depression Scale, Beck Depression Inventory, Brief Evaluation of Medication Influences and Beliefs, Social Support Questionnaire (SSQ), Temperament and Character Inventory, Parental Bonding Instrument (PBI), the Short Form Health Survey (SF-36). Results When evaluating on the basis of abstinence rule, a comparison of ALD-RC and NALD-RC in the preoperative period identified similar patterns of psychosocial characteristics, except that the NALD-RC scored higher on the PBI item “overprotection from mother” (P < 0.05). The only significant difference between ALD-R and NALD-R after liver transplantation was in SSQ scores at 3 months. Conclusion The psychosocial characteristics of ALD-RC and NALD-RC may be similar when evaluated on the basis of Japan’s abstinence rule. This result also imply that the psychosocial characteristics of ALD-RC may differ from the previously reported psychosocial characteristics of alcohol dependent patients. These findings have the potential to provide helpful information for the evaluation of ALD-RC.